Vertikal'naya mekhanicheskaya rabota v aspekte otsenki tekhnika bega - Arakelyan, E. E.; Primakov, Yu. N.; Umarov, A. A.; Tyupa, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The aim of this study was to verify the hypothesis about the correlation between the meanings of vertical swingings when running and the velosity's parameters. 65 sprinters of various qualification acted as the subject of this research. The speed of running and the length of strides, time of support were registrated. It had been revealed that the speed of running's increase correlates with the decrease of the vertical component of external work and the angle of departure. This fact does not prove that it is the specific feature of elite runners technical mastery.